2007
DOI: 10.4049/jimmunol.178.7.4112
|View full text |Cite
|
Sign up to set email alerts
|

Four Functionally Distinct Populations of Human Effector-Memory CD8+ T Lymphocytes

Abstract: In humans, the pathways of memory and effector T cell differentiation remain poorly defined. We have dissected the functional properties of ex vivo effector-memory (EM) CD45RA−CCR7− T lymphocytes present within the circulating CD8+ T cell pool of healthy individuals. Our studies show that EM T cells are heterogeneous and are subdivided based on differential CD27 and CD28 expression into four subsets. EM1 (CD27+CD28+) and EM4 (CD27−CD28+) T cells express low levels of effector mediators such as granzyme B and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
356
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(385 citation statements)
references
References 44 publications
(68 reference statements)
22
356
0
7
Order By: Relevance
“…Natalizumab (Tysabri), a blocking monoclonal blocking Ab against VLA-4 is an approved treatment for MS (38). Moreover, CD8EM T cells have the capacity to migrate to nonlymphoid tissues (39). In the case of MS, they potentially migrate into the CNS, where they re-encounter IL-7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Natalizumab (Tysabri), a blocking monoclonal blocking Ab against VLA-4 is an approved treatment for MS (38). Moreover, CD8EM T cells have the capacity to migrate to nonlymphoid tissues (39). In the case of MS, they potentially migrate into the CNS, where they re-encounter IL-7 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore compared T cell differentiation status in AD patients versus old controls, using multiple markers including the CD27 and CD28 costimulatory molecules, which are crucial for T cell activation. It has been reported that expression of these two markers is reduced proportional to the degree of differentiation of the T cell (Romero et al, 2007). Naïve cells are CD28 + CD27+ while the latest stage of T cell differentiation is accompanied by the loss of both CD28 and CD27 (Koch et al, 2008).…”
Section: Costimulatory Molecules On Cd4+ and Cd8+ Cellsmentioning
confidence: 99%
“…Memory phenotype T cells are further divided into subpopulations according to the combination of these expression levels [13][14][15]. Many studies have revealed that the memory phenotype human T cells existed in the peripheral tissues, depending on the expression levels of adhesion molecules and chemokine receptors [1,2].…”
Section: Introductionmentioning
confidence: 99%